Synthesis, morphology, and thermal stability of nanoporous cyanate ester resins obtained upon controlled monomer conversion. (December 2015) - Fainleib, A.; Gusakova, K.; Grigoryeva, O.; Starostenko, O.; Grande, D.
Graphical abstract: Highlights: A series of CERs with controlled conversion 79–96% of cyanate groups are synthesized. The nanoporous films are obtained via extraction of soluble CERs from the networks. The pore sizes in CER films vary from 10 to 220 at an average diameter of 20–45 nm. Porosity ratios between 2.8 and 7.4% are determined using SEM. Thermal stability of CER films strongly depends on the final curing conditions. Abstract: This paper focuses on the development of a straightforward and effective method for producing nanoporous thermosetting Cyanate Ester Resins (CERs) with controlled conversion of the reactive groups of cyanate monomer by varying polymerization temperature and duration of CER synthesis, followed by a simple extraction procedure. Using Fourier transform infrared spectroscopy, the conversion degree ranging from about 79% up to 96% was determined. DSC-based thermoporometry and scanning electron microscopy analyses evidenced the generation of nanoporous structures in the cross-linked CER films produced. The pore size distribution varied from ∼10 to 220 nm with an average pore diameter of around 20–45 nm and the porosity ratio was comprised between 2.8% and 7.4% for all the nanoporous CERs studied. It was established that the thermal stability of nanoporous CERs remained high enough and depended on the final conversion of cyanate groups in the partly cured CER networks.